Associations between a mixture of phenols and phthalates and child behaviour in a French mother–child cohort with repeated assessment of exposure. (November 2021) - Guilbert, Ariane; Rolland, Matthieu; Pin, Isabelle; Thomsen, Cathrine; Sakhi, Amrit K.; Sabaredzovic, Azemira; Slama, Rémy; Guichardet, Karine; Philippat, Claire
Highlights: Phenols and phthalates were frequently detected in this recent pregnancy cohort. Weighted Quantile Sum indexes were associated with child behaviour. Associations tended to be stronger in girls. Bisphenol A, triclosan, MEP were the main mixture contributors for externalizing score. MEP, MBzP, MnBP were the main mixture contributors for internalizing score. Abstract: Background: Synthetic phenols and phthalates can interfere with biological pathways involved in brain development. Despite the high within-subject temporal variability of urinary concentrations observed for their metabolites, studies investigating effects of phenols and phthalates on child behaviour often relied on a limited number of spot biospecimens to assess exposure. Besides, the majority did not consider mixture effects. Objectives: To study the combined effect of prenatal exposure to synthetic phenols and phthalates on child behaviour using repeated exposure measurements. Methods: We assessed concentrations of 12 phenols, 13 phthalate and 2 non-phthalate plasticizer metabolites in within-subject pools of multiple urine samples (median = 21 samples per individual pool) collected at two distinct time points during pregnancy in 416 mother–child pairs from the French SEPAGES cohort. Child behaviour was evaluated at two years using the Child Behaviour Checklist 1.5–5 (CBCL). Associations between a mixture of biomarkers of exposure and externalizing and internalizing behaviour scores were studied using adjusted Weighted Quantile Sum (WQS) regressions with a repeated holdout validation (100 repetitions). Results: The positive WQS indexes were associated with both the externalizing and internalizing behaviour scores in the whole population, indicating greater risk of behavioural problems. Stratification for child sex suggested stronger associations in girls than boys. On average, girls externalizing and internalizing scores increased by 3.67 points (95% CI: 1.24, 6.10) and 2.47 points (95 %CI: 0.60, 4.33) respectively, for an increase of one tertile in the WQS index, compared with 1.70 points (95 %CI: −0.42, 3.81) and 1.17 points (95 %CI: −0.50, 2.84) in boys. Main contributors for the associations observed in girls were bisphenol A (weight of 18%), triclosan (17%) and monoethyl phthalate (MEP, 15%) for the externalizing score and MEP (19%), mono-benzyl phthalate (MBzP, 19%) and mono-n-butyl phthalate (MnBP, 16%) for the internalizing score. Discussion: Our results suggest adverse associations between in utero exposure to a mixture of phenols and phthalates and child behaviour, mainly in girls. Public health consequences may be substantial due to the widespread exposure of the population to these compounds.